Sources of Information on Flood-Resistant Design and Construction - Regina Fegan; Michael T. Olexa (EDIS)
The primary purpose of the publications referenced in this article is to assist engineers, architects, contractors, and property owners in locating detailed information on how to design and construct flood-resistant buildings and structures. This document, IFAS publication DH0435, was published June 1998, revised May 2003. It is part of The Disaster Handbook, a component of the Comprehensive Disaster Preparedness and Recovery Education Module.